Animals & Women : Feminist Theoretical Explorations - Carol J. Adams; Josephine Donovan (Bloomsbury, 1995)
This wide-ranging multidisciplinary anthology presents original material from scholars in a variety of fields, as well as a rare, early article by Virginia Woolf. Exploring the leading edge of the species/gender boundary, it addresses such issues as the relationship between abortion rights and animal rights, the connection between woman-battering and animal abuse, and the speciesist basis for much sexist language. Also considered are the ways in which animals have been regarded by science, literature, and the environmentalist movement. A striking meditation on women and wolves is presented, as is an examination of sexual harassment and the taxonomy of hunters and hunting. Finally, this compelling collection suggests that the subordination and degradation of women is a prototype for other forms of abuse, and that to deny this connection is to participate in the continued mistreatment of animals and women.
English
Keywords: HQ1-2044 The Family. Marriage. Women- Feminism/Ecofeminism